(untitled) (Altre Modernità, 2020)
Set in the tradition of studies that look at digital interactions, this paper aims to explore the dimension of illness as referred to by informal caregivers in online exchanges. The research attempts to a) describe posts as mediated illness stories by comparing them to the storytelling in interaction model (Mishler), and b) explore what is revealed about the writer. A data set of 7371 posts (including sub-replies) has been studied as personal narratives in non-clinical therapeutic exchanges by means of Digital Conversation Analysis (Giles et al.), and investigated as written emotional disclosure (Pennebaker). Posts are found to convey explicit and implicit messages to be understood and incorporated into health promotion efforts, beliefs and issues. The paper makes a contribution to the field of medical humanities by proposing online posts as third-person accounts of illness experiences, and as the linguistic manifestation of caregivers’ (CGs) state of mind. Although digital settings have already been studied in the context of medical exchanges, this is the first study involving informal caretakers’ exchanges.